Antinociceptive Properties of Protein C in a Model of Inflammatory Hyperalgesia in Rats - Pichler, L; Schramm, W; Ulrich, W; Varadi, K; Schwarz, H P (Thrombosis and Haemostasis, 1995)
We investigated the role of human protein C in an animal model of inflammatory hyperalgesia. Pain was induced by intraplantar injection of carrageenan (3 mg) into the hind paw of rats. The pain threshold was measured by exerting increasing amounts of pressure (in mmHg) on the paw until a struggle reaction was observed. Protein C (8-800 IU/kg) was administered intravenously immediately after carrageenan. Controls received either intraplantar injections of saline (100 µ1) instead of carrageenan or carrageenan alone. Effects on pain threshold were expressed in percent of the pretreatment value. Carrageenan alone lowered the mean pain threshold after 3 h to 33.2 ± 2.2% of the pretreatment level. Addition of protein C resulted in a dose-dependent rise in pain threshold towards the level observed in control animals treated with saline instead of carrageenan (pain threshold after 800 IU/kg protein C = 62.9 ± 2.3% of pretreatment level), demonstrating an antinociceptive effect. Protein C had no effect in animals not preconditioned with intraplantar carrageenan. Thus protein C clearly antagonized the inflammatory pain induced by carrageenan. The antinociceptive action of protein C was antagonized by injection of a monoclonal antibody against protein C, providing additional evidence that the effect was protein C-mediated.